Possível influência de variáveis meteorológicas na morbidade hospitalar causada por pneumonia na cidade de Belém-PA - LOPES, Clésio Baia (2019)
The present study relates the data of morbosity hospitalar caused by pneumonia,in the city of Belém-Pa, for two age groups being the first of 0-14 years and monday above 60 years, with the temperature of the air, precipitation pluviométric and relative humidity of the air for the period of 1997 the 2007. The monthly data of morbosity hospitalar caused by pneumonia were supplied by the Secretary of Public Health of the State of Pará (SESPA) and the temperature data, precipitation and relative humidity of the air were supplied by the 2º District of Meteorology (2º DISME). They were appraised 3 (three) months of the rainy period (February, March, April), 3 (three) months of transition ( June, July, August) and 3 (three) months of the less rainy period (October, November, December) . It was verified that for the (above 60 years) 0-14 year-old age group the effects of the meteorological variables seem to be more significant when if compared with the other age group. It is also that for children of 0-14 years the highest rates of pneumonia occur in the transition period and this is due, possibly, that the body of children in this age group is most vulnerable to climate change. It is concluded that the most significant variable for the occurrence of morbidity is the rainfall and that, possibly, to the fact that during this period people are more clustered indoors facilitating the infection by viruses, bacteria or fungi, factors those causing the illness.